2020
DOI: 10.2147/opth.s253370
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of 190 μg Fluocinolone Acetonide and 700 μg Dexamethasone Intravitreal Implants in Diabetic Macular Edema Using the Area-Under-the-Curve Method: The CONSTANT Analysis</p>

Abstract: Purpose: Calculations of area-under-the-curve (AUC) provide the average letters gained across the entire treatment period, which may be a better estimate of long-term effectiveness than single time-point outcomes, particularly when it comes to sustained-release therapies. Materials and Methods: The AUC method was used to compare the efficacy of the 0.2 µg/day fluocinolone acetonide (total dose of 0.19 mg; FAc) and dexamethasone (DEX) 700 µg implants based on published data from their respective Phase 3 FAME (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…FAc implant is approved in Europe for the treatment of diabetic macular edema (DME) and NIU-PS [ 5 ]. The efficacy of the implant has been recently evaluated with an area under the curve (AUC) approach in eyes with DME [ 6 ]. No such analysis has been employed in the uveitis field.…”
Section: Introductionmentioning
confidence: 99%
“…FAc implant is approved in Europe for the treatment of diabetic macular edema (DME) and NIU-PS [ 5 ]. The efficacy of the implant has been recently evaluated with an area under the curve (AUC) approach in eyes with DME [ 6 ]. No such analysis has been employed in the uveitis field.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we do acknowledge that the AUC analysis does have limitations and that these have been acknowledged in the manuscript and are based on the retrospective nature of the analysis as well as the comparison of different study protocols and patients. 6 However, the 190 µg fluocinolone acetonide implant's constant and near zeroorder drug release kinetics 7 means it is less affected by the timing of appointments and delayed injections, and is a key design feature that has long-term benefits for patients with diabetic macular edema.…”
Section: Dear Editormentioning
confidence: 99%
“…In a recent edition of Clinical Ophthalmology, Zarranz-Ventura and Mali presented 1 an area-under-the-curve (AUC) analysis that directly compared the best corrected visual acuity (BCVA) improvements in the pivotal diabetic macular edema (DME) trials (FAME and MEAD) for the fluocinolone acetonide implant (Iluvien) and the dexamethasone implant (Ozurdex). They concluded that patients in FAME had superior BCVA improvement over the course of 36 months.…”
Section: Dear Editormentioning
confidence: 99%